The Effectiveness of Oral Corrective Feedback in the Acquisition of Third-Person Singular‘s’ in Iranian EFL Context - Navid Bahrami Malek; Ali Akbar Ansarin; Yaser Hadidi (Journal of Modern Research in English Language Studies)
Focus on form through oral corrective feedback has been the center of many L2 learning investigations in recent decades. Although research has been abundantly done on the impact of different single-feedback types, not many studies have included combinational feedback strategy, especially as regards the mastery of both explicit and implicit knowledge of morpheme ‘s’ by EFL students in Iran. Therefore, the present work attempted to compare the effectiveness of unmarked recast, explicit correction with metalinguistic explanation, and mixed feedback in the expansion of knowledge of third-person marker ‘s’ in Iranian task-based language teaching context, employing a pretest/posttest design. To this end, forty-eight lower-intermediate learners of EFL were selected as participants. Every feedback type was supplied to an experimental group through story retelling and picture description tasks. Control group, however, was not provided with any intervention and feedback. Untimed grammaticality judgment and elicited oral imitation tests were used as measurement tools. Results of Descriptive Statistics, One-Way Between Groups ANCOVA and Tukey’s Multiple Comparison Post-Hoc Test illustrated that all types of feedback were relatively effective. Nevertheless, mixed feedback and explicit correction with metalinguistic explanation lead to overall acquisition. The insights provided might benefit EFL instructors in Iran in employing the best way(s) of corrective feedback to foster language learning in task-based teaching approach, which can promote Iranian English learners’ acquisition of third person singular‘s’.